Pharmacokinetics Guided Personalized Management of Hemophilia Rehabilitation: A Chinese Consensus Based on Modified Delphi - Hemophilia Treatment Center Collaborative Network of China (罕见病研究)
Hemophilia is a collection of hereditary bleeding disorders that are X-linked recessive. Patients often experience recurrent bleeding in joints, leading to a cascade of complications including chronic synovitis, hemophilic arthropathy, muscle atrophy, and joint contractures. These issues are the primary causes of functional impairment and disabilities in individuals with hemophilia. Rehabilitation focusing on physical function is crucial in the multidisciplinary management of hemophilia. Nineteen experienced consensus experts invited by the Hemophilia Treatment Center Collaborative Network of China participated in the formulation of the Chinese consensus. Utilizing the modified Delphi method, the experts reached a consensus on nine recommendations for the formulation of hemophilia recovery plans, personalized management under the guidance of pharmacokinetics, and postoperative recovery treatment for orthopedic surgery, providing standardized procedures for evaluating and tailoring rehabilitation for hemophilia patients. Additionally, the investigation results of 22 physiotherapists on the risk assessment of various rehabilitation scenarios were further summarized for clinical reference.